How workers let artificial intelligence recruit and dismiss? - Jaehyun Lee; Jihye Lim; Junseok Hwang; Junmin Lee (International Telecommunications Society (ITS), 2024)
As artificial intelligence (AI) advances, it has become involved in decision-making that can significantly affect people's lives. Organizations have adopted AI in their human resource planning which makes decisions over workers and impacts their livelihoods. For the impact of decisions, it can potentially lead to conflicting opinions within organizations. When workers form their opinions on AI decision-making, how do the counterparts surrounding them, namely the organization and the AI, affect their opinions? To answer this question, we analyze how workers' trust created by the organization and their perceptions arising from the AI influence their opinions on allowing AI to make decisions of recruitment and dismissal. We find that workers' trust in organizational management of AI significantly affects their permission for AI to decide who is recruited and dismissed. Also, we confirm that workers' perceptions on AI are significant factors influencing their trust in organizational management of AI. Our findings suggest that in organizations where workers' trust in organizational management of AI is established, AI can be applied to make critical decisions about individuals. These results imply that as AI becomes more commonly involved in organizations' decision-making, the role of managing trust within organizations will become increasingly significant.
Keywords: 330; artificial intelligence; worker trust; organizational decision; human resource; decision making